Triple flap meatoplasty for acquired meatal atresia - Munjal, Manish; Rishi, Porshia; Sidhu, Harjinder; Munjal, Shubham; Talwar, Shivam; Sharma, Salony; Chawla, Deeksha; Dhillon, Karan (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Surgical intervention was undertaken in post-traumatic cartilaginous meatal atresia with an intact tympano-ossicular assembly, utilizing a triple flap meatoplasty, to achieve a wide meatus. The intricacies of the procedure with the late outcome are being discussed.